Discovery and development of oseltamivir at Gilead Sciences. Issue 1 (12th April 2022) - Schmitz, Uli; Swaminathan, Swami
John Martin's untimely death in March 2021 was a huge loss for us personally, Gilead Sciences, the company he built over 30 years and the scientific community concerned with antiviral therapies. We wish to honor John's legacy by retelling the discovery and history of Tamiflu and his contributions to it. Without his vision, persistence, and keen eye for opportunities, Tamiflu would not exist and Gilead's path would not have been the same. His strategic thinking around the first oral flu drug is still quite relevant today, when we are still in the SARS-CoV-2 pandemic. John explained it simply in an interview with the Science History Institute in May 2020: "… most of my colleagues, we travel with Tamiflu when we go internationally, because it works for treatment and prevention, and hopefully, there will be a solution like that, eventually, for the Covid virus in addition to vaccines. Most people will get a flu vaccine every year, but there is still disease, we need a pill for treatment and prevention. "